Acute Renal Failure and Severe Hypertension from a Page Kidney Post-Transplant Biopsy - Maria Aurora Posadas; Vincent Yang; Bing Ho; Muhammad Omer; Daniel Batlle (The Scientific World Journal)
Page kidney refers to a clinical picture characterized by acute onset of hypertension due to external compression of the kidneys from hematoma, tumor, lymphocele, or urinoma. Hypertension is believed to result from renin-angiotensin-aldosterone activation triggered by renal hypoperfusion and microvascular ischemia. Renal failure, in addition to hypertension, may occur in the setting of a single functional kidney or a diseased contralateral kidney. We report a case of a patient who had a transplant kidney biopsy complicated by a subcapsular perinephric hematoma. The patient presented with an acute increase in blood pressure and a rapid rise in serum creatinine following a transplant kidney routine biopsy. He underwent emergent evacuation of the perinephric hematoma, with consequent decrease of his blood pressure and return of serum creatinine back to his baseline level. Early recognition and rapid intervention are needed in order to correct hypertension and reverse acute renal failure in Page kidney occurring in renal transplant recipients.